Ability of Ectoine to Stabilize Lipase against Elevated Temperatures and Methanol Concentrations - I Putu Parwata; Deana Wahyuningrum; Sony Suhandono; Rukman Hertadi (Universitas Gadjah Mada, 2021)
Ectoine is one of the compatible organic molecules that can protect the protein from heating, freezing, and chemicals contact. This study aims to investigate the ability of ectoine to stabilize lipase on heating and in methanol treatments as an effort to provide a stable biocatalyst for the production of biodiesel. Various ectoine concentrations were added to lipase solutions, then the mixture was heated, and the residual activity of the lipase was determined. Similar steps were also conducted for methanol treatment. The results showed that ectoine maintained and even improved the catalytic activity of lipase after treatment with either heat or methanol. The addition of ectoine to a final concentration of 110 to 150 mM could maintain lipase activity up to 80% when heating to approximately 95 °C. Additionally, more than 20% of lipase activity increased on heating to temperatures below 75 °C in the presence of ectoine at a final concentration of 25 to 120 mM. Meanwhile, after incubation in methanol at a level of around 84% (v/v), the activity of lipase containing 40–90 mM ectoine was maintained. These results demonstrated that ectoine was highly effective in protecting lipase from heat and methanol.